Attenuated Streptococcus agalactiae WC1535 ∆Sia perturbs the gut microbiota of Oreochromis niloticus, massively colonizes the intestine, and induces intestinal mucosal immunity after intraperitoneal inoculation - Hao, Jingwen; Wang, Shuyi; Yang, Jicheng; Zhang, Qianqian; Wu, Zhenbing; Zhang, Defeng; Li, Aihua (Frontiers in Microbiology, 2022)
We previously developed and assessed the effectiveness of the attenuated Streptococcus agalactiae (Group B Streptococcus, GBS) strain WC1535 ∆Sia (with neuA-D gene cluster deletion) vaccine in tilapia (Oreochromis niloticus). In this study, we characterized the bacterial communities of the tilapia intestines by 16S rRNA high-throughput sequencing and assessed the serum antibody response, expression of immune-related genes, and histological changes following formalin-killed GBS vaccine (FKV) and the live attenuated vaccine ∆Sia (LAV). Results showed that FKV and LAV induced robust systemic and intestinal mucosal immune responses in tilapia without causing obvious pathological changes in the hindgut, spleen, and head kidney but exerted different effects on intestinal bacterial communities. The richness or diversity of the intestinal bacterial community of FKV tilapia showed no significant changes compared with that of the control fish (p > 0.05) at either day 21 post-initial vaccination (21 dpiv) or day 35 (day 14 after the second immunization) (35 dpiv). The community composition of FKV tilapia and controls was significantly similar, although the relative abundance of some genera was significantly altered. Relative to control fish, the gut ecosystem of LAV tilapia was significantly disturbed with a substantial increase in community diversity at 21 dpiv (p < 0.05) and a significant decrease at 35 dpiv in fish with high serum antibody response (ΔSia35H) (p < 0.05). However, there was no significant difference between ΔSia35H and ΔSia35L (low serum antibody response) fish (p > 0.05). Moreover, the community composition of LAV tilapia at 21 dpiv or 35 dpiv was considerably different from that of the controls. Particularly, GBS ∆Sia was found to be abundant in the intestine at 21 and 35 dpiv. This result suggested that the parenteral administration of the LAV (∆Sia) may also have the effect of oral vaccination in addition to the immune effect of injection vaccination. In addition, a significant correlation was found between the expression of immune-related genes and certain bacterial species in the intestinal mucosal flora. Our findings will contribute to a better understanding of the effects of inactivated and attenuated vaccines on intestinal gut flora and their relationship with the immune response.